2018
DOI: 10.1002/celc.201801229
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Ion‐Transport Mechanism of Li7(Al0.1)La3Zr2O12 Solid Electrolyte Modified by using a Spark Plasma Sintering Method

Abstract: A novel interfacial in situ modification for Li7(Al0.1)La3Zr2O12 is designed and prepared by using a spark plasma sintering method. The modified interface with most grain boundary area exhibits excellent interfacial electrochemical properties. The X‐ray diffraction (XRD) and scanning electron microscope (SEM) data indicate that the interfacial modified specimen (spark plasma sintering method, 1000 °C, 5 min) with 38.2(6) nm grain diameter and 32,134 cm2/g grain boundary specific surface area has the highest io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A number of oxide‐based and nonoxide‐based SSEs exhibiting superb ionic conductivity have been investigated, such as Li‐β‐alumina, Li 3 N, Li 4 SiO 4 , perovskite‐type Li 3 x La 2/3−x TiO 3 (LLTO), garnet‐type Li 7 La 3 Zr 2 O 12 (LLZO) and sodium superionic conductor (NASICON)‐type Li 1.2 Al 0.2 Ti 1.8 (PO 4 ) 3 (LATP), as shown in Table . In recent studies, OCEs have shown great promise due to their chemical stability in air, high ionic conductivity of 10 −3 S cm −1 (25 °C), wide electrochemical window and excellent mechanical strength . Although the thin‐film electrolyte LiPON has a very low ionic conductivity of 10 −6 S cm −1 , the area specific resistance (ASR) of the electrolyte is as low as 10 Ω cm −2 due to its thin thickness (below 1 μm).…”
Section: Oces In Asslbsmentioning
confidence: 99%
“…A number of oxide‐based and nonoxide‐based SSEs exhibiting superb ionic conductivity have been investigated, such as Li‐β‐alumina, Li 3 N, Li 4 SiO 4 , perovskite‐type Li 3 x La 2/3−x TiO 3 (LLTO), garnet‐type Li 7 La 3 Zr 2 O 12 (LLZO) and sodium superionic conductor (NASICON)‐type Li 1.2 Al 0.2 Ti 1.8 (PO 4 ) 3 (LATP), as shown in Table . In recent studies, OCEs have shown great promise due to their chemical stability in air, high ionic conductivity of 10 −3 S cm −1 (25 °C), wide electrochemical window and excellent mechanical strength . Although the thin‐film electrolyte LiPON has a very low ionic conductivity of 10 −6 S cm −1 , the area specific resistance (ASR) of the electrolyte is as low as 10 Ω cm −2 due to its thin thickness (below 1 μm).…”
Section: Oces In Asslbsmentioning
confidence: 99%
“…However, while the ion transport mechanisms in bulk LGPS have been investigated, this is not the case for nanocrystallite effects in LGPS samples. Grain boundary resistance in sulfide solid electrolytes is generally considered to be minimized compared to that of oxide systems. Beyond LGPS, there are several studies concerning the nanostructure of various solid electrolytes in order to reduce interfacial resistance and improve ion transport. The influence of nanosizing crystalline samples on Li-ion conductivity has been illustrated for sulfide and oxide solid electrolyte materials. However, the atomistic effects of nanosizing LGPS have not been previously characterized.…”
mentioning
confidence: 99%
“…Beyond LGPS, there are several studies concerning the microstructure and grain boundaries of various solid electrolytes in order to reduce interfacial resistance and improve ion transport [31][32][33][34][35][36][37][38] . The influence of nanosizing crystalline samples on Li-ion conductivity has been illustrated for sulfide [38][39][40] and oxide [41][42][43] solid electrolyte materials.…”
mentioning
confidence: 99%